A simple and accurate method for specific quantification of biomass in mixed cultures of filamentous fungi by quantitative PCR - Reyes-Calderón, Alonso (2020)
Production of lignocellulolytic enzymes by filamentous fungi have a great potential at industrial level due to their widespread applications. Mixed fungal cultures and particularly mixed fungal biofilms constitute a promising fermentation system for an enhanced enzyme production. However, it has not been addressed how much of this enhancement depends on the mixed biomass proportion. In this sense, the aim of this study was to develop a method to specifically and accurately quantify mixed fungal biomass. For this purpose, mixed biofilm cultures composed of Aspergillus niger and Trichoderma reesei, two filamentous fungi used industrially for cellulase production, were collected from 48 to 120 h of growth; mycelia were pulverized, and DNA was extracted for qPCR assays with specific primers for each fungus. Primers were designed from non-conserved regions of sequences of actin and β-tubulin genes of both A. niger and T. reesei. Specificity of these primers was tested in silico and experimentally. A statistically significant correlation was obtained between qPCR-calculated biomass and dry weight biomass data. By this method, it was possible to detect changes on mycelia proportions in biofilms over time, suggesting a competitive interaction between these two fungi. In conclusion, this method allows a specific and accurate quantification of mixed fungal biomass and could be also applied to different mixed culture systems for studying microbial interactions.